(untitled) (Journal of the College of Basic Education, 2024)
This research is entitled: Mosques manifestations in the interpretation of the Koran, Moin al-Din al-Aji (d. 905 AH) -Surah Fatir as a model-, -Study and investigation. Importance of the topic There is no doubt that the process of verifying manuscripts is today one of the necessary studies. Especially if we know that a large part of our heritage is still written from here, any historical progress is linked to the extent of progress of researchers in excavation and research within the heritage; To bring these manuscripts to light, and to achieve an academic investigation; In order to be able to benefit from it, the aim of the letter is to bring a treasure of our great Islamic heritage to light, bearing in mind that many manuscripts are still unpublished or investigated, and they require a great effort to reach us Reasons for choosing the topic The most important reasons for choosing this topic is to serve the Book of God Almighty and the purified Sunnah of His Holy Messenger (may God bless him and grant him peace), and to highlight its benefits to people. In order for them to learn to work with them, through the verification of manuscripts and contributing with the effort of Al-Muqal in showing what has been lost from the Islamic heritage, and highlighting the exploits of the prominent imams, Islamic scholars, and clarifying the scientific value of the manuscript .Search Plan After this introduction, the research plan necessitated that it be in one section only. and he: Investigation Section: In it, I investigated (Surah Fater)